PEMANFAATAN LIMBAH BUBUT BESI PADA BETON SERAT DITINJAU DARI KUAT TEKAN DAN KUAT LENTUR - Hanggara, ST., MT, Ikrar (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2019)
The practice of steel lathing by students of Mechanical Engineering State Polytechnic of Malang produces an abundant amount of steel fiber waste. In this research steel fiber was utilized to substitute coarse aggregate in fiber concrete mixture. The purpose of this research is to find out the compressive and flexure strengths of fiber concrete carried out at Material Laboratory Civil Engineering Politeknik Negeri Malang, and to estimate the cost. The required data were of the results of coarse aggregate and fine aggregate tests, and physical cutting of steel lathing waste. Mix design concrete referred to SNI 03-2834-2000. Compressive strength test used 54 cylindrical specimens of Ø15 x 30cm varied at 0%, 5%, and 10% substitutions. Tests were carried out on concrete aged 7, 14, and 28 days. The flexural strength test used 6 beam specimens of 15 x 15 x 60cm varied at 0%, 5%, and 10% substitution. Tests were carried out on 28 days of concrete. The experiment resulted in 39.01 Mpa compressive strength at 0% variation; 24.54 Mpa compressive strength at 5% variation; 21.80 Mpa compressive strength at 10% variation; in 3.87 Mpa flexure strength at 0% substitution; 4.27 Mpa flexure strength at 5% substitution; 4.07 Mpa flexure strength at 10% substitution. The greatest result of flexure strength test occured at 5% variation; at Rp.940,276/m3 at 0% variation and at Rp.938,719/m3 at 5% variation or 0.2 % decrease. Key word : Steel lathe waste, compressive strength, flexure strength